Heterorhabditis and Photorhabdus Symbiosis: A Natural Mine of Bioactive Compounds - Parihar, Ripu Daman; Dhiman, Urvashi; Bhushan, Anil; Gupta, Prashant Kumar; Gupta, Prasoon (Frontiers in Microbiology, 2022)
Phylum Nematoda is of great economic importance. It has been a focused area for various research activities in distinct domains across the globe. Among nematodes, there is a group called entomopathogenic nematodes, which has two families that live in symbiotic association with bacteria of genus Xenorhabdus and Photorhabdus, respectively. With the passing years, researchers have isolated a wide array of bioactive compounds from these symbiotically associated nematodes. In this article, we are encapsulating bioactive compounds isolated from members of the family Heterorhabditidae inhabiting Photorhabdus in its gut. Isolated bioactive compounds have shown a wide range of biological activity against deadly pathogens to both plants as well as animals. Some compounds exhibit lethal effects against fungi, bacteria, protozoan, insects, cancerous cell lines, neuroinflammation, etc., with great potency. The main aim of this article is to collect and analyze the importance of nematode and its associated bacteria, isolated secondary metabolites, and their biomedical potential, which can serve as potential leads for further drug discovery.